2005
DOI: 10.1590/s0100-204x2005000200007
|View full text |Cite
|
Sign up to set email alerts
|

Deficiências de macronutrientes no estado nutricional da mamoneira cultivar Iris

Abstract: Resumo -Os objetivos deste trabalho foram avaliar o efeito da deficiência dos macronutrientes no crescimento e estado nutricional da mamoneira (Ricinus communis L.) e a obtenção do quadro sintomatológico das deficiên-cias de N, P, K, Ca, Mg e S. Cultivou-se Ricinus communis L. cultivar Iris em solução nutritiva, tendo como tratamentos soluções completa e deficientes em N, P, K, Ca, Mg e S. Foram determinadas a concentração indireta de clorofila, a atividade da redutase do nitrato, os teores solúveis de N (NO 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 9 publications
0
9
0
8
Order By: Relevance
“…Physic nut response to N fertilization in Quartzarenic Neossol, in the plant growth stage, in this study, was not consistent with the results observed by Guimarães (2008) for the same species. In castor bean, a species of the same family as physic nut, growth was reduced when N was omitted (Lavres Júnior et al, 2005) but in another study, on the contrary, the growth was not reduced when no N was applied (Nakagawa et al, 1994). Possibly, physic nut is a species with low N demand at the initial stage of vegetative growth, even in soil with low organic matter content (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Physic nut response to N fertilization in Quartzarenic Neossol, in the plant growth stage, in this study, was not consistent with the results observed by Guimarães (2008) for the same species. In castor bean, a species of the same family as physic nut, growth was reduced when N was omitted (Lavres Júnior et al, 2005) but in another study, on the contrary, the growth was not reduced when no N was applied (Nakagawa et al, 1994). Possibly, physic nut is a species with low N demand at the initial stage of vegetative growth, even in soil with low organic matter content (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the culture of castor bean, Lavres et al (2005) reported that the total dry matter production of plants is affected by deficiencies of macronutrients, and that the most limiting element is N, but the need of each element varies depending on the plant species.…”
Section: Resultsmentioning
confidence: 99%
“…It is already known that nitrogen supply increases potassium uptake and also increases protein and soluble amino acid contents, resulting in increased production (Lavres Junior et al, 2005). In this sense, the absence of nitrogen reduces the potassium uptake and, as a consequence, the K content in plants.…”
Section: The Lack O Experimenmentioning
confidence: 99%